“What do you Mean by Masculinity?”: Comparison of Answers of Men with and without Suicidal Thoughts - Grigienė, Dovilė; Guogaitė, Greta; Dadašev, Said; Rimkevičienė, Jurgita; Skruibis, Paulius; Gailienė, Danutė (Psichologija, 2022)
Male suicides are often associated with masculinity norms that encourage certain behaviours that increase the risk of suicide. For example, research shows that restricted emotionality, avoidance of seeking help and self-reliance are associated with higher suicide risk. However, these pre-formulated aspects of masculinity do not necessarily reflect men’s subjective opinions of what masculinity is to them. Researchers argue that it is important to consider personal views about what masculinity is, not only stereotypes about masculinity. The aim of this study is to reveal and compare the subjective opinions about the masculinity of men with and without suicidal ideation. 281 men answered the open-ended question during the survey: “What does masculinity mean to you?”. The answers were analyzed using a content analysis method. We transformed qualitative data into quantitative and compared them statistically between two groups: men with and without suicidal ideation. It turned out that men with suicidal thoughts were more likely to mention that masculinity is the control of emotions, intelligence, and decision-making. Men without suicidal thoughts were more likely to mention family and caring for it as essential aspects of masculinity. The results showed that certain aspects of masculinity might be related to higher risk for suicide, but the study also revealed the masculinity that might be a source of coping.
Keywords: male suicide; masculinity; risk factors; protective factors